(untitled) (International Journal of Mathematics and Physics, 2012)
The partial radial distribution functions and static structure factors of hydrogen-like two component plasmas modeled with the Kelbg pseudopotential are calculated within the Ornstein-Zernike approximation. It is shown that the simulation data on the inverse dielectric function satisfies five convergent sum rules and other exact relations. The sum rules which are the power frequency moments of the loss function, which determines the polarizational stopping power of a plasma characterized by the inverse dielectric function are computed using the Kelbg potential. Results on long-wavelength values of the loss function power moments calculated from the simulation data in comparison to the exact values are presented.